G39 Analysis of parent videos from the #notanurse_but campaign. (24th May 2017) - Wilkinson, C; Bray, L; Keating, P; Carter, B
Abstract : Aims: This paper reports on a project which analysed parentrecorded video diaries from a parent-driven campaign, #notanurse_but, supported by WellChild. The videos aimed to reveal family life and the challenges that parents face providing high level, ongoing clinical care for their son or daughter who has complex care needs. Methods: A team of four researchers (three nurses and one social scientist) analysed 30 videos from the WellChild Website, WellChild Facebook page, a dedicated #notanurse_but campaign Facebook page, YouTube and Twitter. An interpretive, inductive qualitative analytical approach was utilised. At least two researchers analysed each video. Analysis involved repeated viewing of the video and documenting descriptive and interpretive information on a data extraction template. Data included the filming and editing techniques used, actors and props, the key message of the video; the perspectivity (motivation) either specifically described or alluded to; and the overall affect/impact of the video. The videos ranged in length from eight seconds to more than nine minutes. Results: The content of the videos covered a range of activities, including: morning routine; night time routine; undertaking specific medical procedures; and administering medicines. Analysis revealed that videos have most impact when they demonstrate an emotional connexion between the main narrator (typically the parent/carer) and their child. We also found that, generally, videos published on Facebook had more views, 'likes' and interactions than those published on YouTube, suggesting that this is likely the most successful location for WellChild to publish future campaign videos. Although the use of a hashtag in the campaign title (#notanurse_but) is indicative of a Twitter campaign, we found that Twitter was the most under-utilised of all social media platforms, both by parents posting the videos and WellChild sharing the videos. Conclusion: Parent-produced videos reveal the everyday challenges faced and managed by parents of children with complex health care needs. The videos demonstrate the tensions between having to provide highly skilled health care interventions and sustaining the role of mother or father. Our paper best aligns with the following RCN theme: Transforming care for children and young people with continuing care needs and their families